Math Challenge - July 2021

  • Challenge
  • Thread starter fresh_42
  • Start date
  • Featured
  • #76
15,542
13,639
For 3. The kernel of the adjoint map is the centre. Semisimple Lie algebras have trivial centre. For the second part, take a 1d algebra, then the general linear algebra over it is also 1d algebra, hense they are isomorphic. And the abelian algebra is not semisimple.
Yes, and a bit more detailed:

A semisimple Lie algebra has no Abelian ideals. Its center, however, is an Abelian ideal. Thus we have
\begin{align*}
\mathfrak{Z(g)}&=\{\,Z\in \mathfrak{g}\,|\,[X,Z]=0\;\forall \,X\in \mathfrak{g}\,\}\\&=\bigcap_{X\in \mathfrak{g}}\operatorname{ker}\mathfrak{ad}X = \operatorname{ker}\mathfrak{ad} = \{\,0\,\}
\end{align*}
This means that ##\mathfrak{ad}\, : \,\mathfrak{g}\longrightarrow \mathfrak{gl(g)}## is a monomorphism of Lie algebras and
$$
\mathfrak{g} \cong \mathfrak{ad(g)} \cong \mathfrak{Der(g)} \subseteq \mathfrak{gl(g)}
$$
The adjoint representation cannot be onto, since the center of ##\mathfrak{gl(g)}## are all multiples of the identity matrix

If we consider the non Abelian two dimensional Lie algebra defined by ##[X,Y]=Y##, which is the Borel subalgebra of the simple Lie algebra ##\mathfrak{sl}(2)##, or the Lie algebra of matrices ##\begin{bmatrix}*&*\\0&0\end{bmatrix}##, then we have a solvable and therewith no semisimple Lie algebra which has only a trivial center, too. Hence the condition of semisimplicity is not necessary.

As already mentioned says Ado's theorem, that any finite-dimensional Lie algebra over a field of characteristic zero can be seen as a subalgebra of ##\mathfrak{gl}(n)## for sufficiently large ##n.##
 
  • #77
144
62
I'm pretty unsure about this solution. Linear algebraic groups over finite fields is new territory to me, but I think I managed to leverage some of my abstract algebra knowledge.

We start over the general finite field ##\mathbb{F}_q##:
$$|\mathrm{GL}(2,q)|=(q^2-q)(q^2-1)$$ a well known formula which can be deduced by fixing a nonzero vector for the first column (of which there are ##q^2-1##), and counting the number of linearly independent vectors as possible values for the second column (of which there are ##q^2-q## for each vector in the first column).

From here on out we assume that ##-1## is a nonresidue modulo ##q##, so that ##\mathbb{F}_q{[}i{]}## is a quadratic field extension with ##i^2=-1##. (##q=19## happens to satisfy this property.) We next make use of a representation of ##\mathrm{GL}(2,q)## over ##\mathbb{F}_{q^2}##. Choose the following basis for ##M(2,q)##: $$\mathbf{1} = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix},\quad \mathbf{i} = \begin{bmatrix} 0 & 1 \\ -1 & 0 \end{bmatrix},\quad \mathbf{j} = \begin{bmatrix} 0 & 1 \\ 1 & 0 \end{bmatrix},\quad \mathbf{k} = \begin{bmatrix} 1 & 0 \\ 0 & -1 \end{bmatrix}$$ Also known as the split-quaternions, we have a 2-dimensional representation over ##\mathbb{F}_{q^2}## via the following isomorphism:
$$w\mathbf{1}+x\mathbf{i}+y\mathbf{j}+z\mathbf{k}\Rightarrow\begin{bmatrix} w + xi & y + zi \\ y - zi & w - xi \end{bmatrix} = \begin{bmatrix} u & v \\ v^* & u^* \end{bmatrix}$$ The center of the split-quaternions consists of scalar matrices over ##\mathbb{F}_{q^2}##, of which there are ##q^2-1##. Hence, we have ##\mathrm{GL}(2,q)\triangleright\mathrm{PU}(Q,q^2)##. The latter group is the 2-dimensional projective unitary group with respect to the Hermitian form ##Q=\begin{bmatrix} 1 & 0 \\ 0 & -1\end{bmatrix}##, the form derived from the norm on the split quaternions ##|u|^2-|v|^2##. Its order is ##q(q-1)##.

We restate the following of the Sylow theorems for clarity: the number of conjugates of the Sylow ##p##-subgroup of a group ##G##, ##n_p##, satisfies ##n_p\equiv 1\, (\mathrm{modulo}\,p)## and ##n_p|[P : G]## where ##P## is any Sylow ##p##-subgroup.

The Sylow ##p##-subgroup of order ##q## can be generated by the element $$1+\frac{1}{2}(\mathbf{i}+\mathbf{j})$$which maps to the matrix ##\begin{bmatrix} 1 & 1 \\ 0 & 1 \end{bmatrix}## in the original representation over ##\mathbb{F}_q##. Observe that the Sylow ##q##-subgroup must be normal: ##n_q## divides ##q-1## and must have remainder 1 when divided by ##q##, implying the subgroup only has one conjugate. Since ##q## is prime, the Sylow ##q##-subgroup is isomorphic to ##C_q##.

Now we restrict our attention to the case ##q=19##. We have ##\mathrm{PU}(Q,q^2)\cong C_q\times G##, where ##|G|=19-1=2\cdot 3^2##. By inspection, we see that the Sylow ##3##-subgroup must be normal, since ##n_3## must divide ##2## and have remainder 1 when divided by ##3##. Note that the equivalence class of the element ##5+10\mathbf{j}## in ##\mathrm{PU}(Q,19^2)## has order ##9## (since the smallest ##n## such that ##(5+10\mathbf{j})^n## is scalar is ##9##), generating a cyclic subgroup of order 9, thus the Sylow ##3##-subgroup in ##G## is isomorphic to ##C_9##.

In total, we have ##\mathrm{GL}(2,19)\cong\mathbb{F}_{19^2}^\times\rtimes\mathrm{PU}(Q,19^2)##, and ##\mathrm{PU}(Q,19^2)\cong C_{19}\rtimes (C_9\rtimes C_2).## The composition factors are thus: $$\mathrm{GL}(2,19)\cong (C_{8}\times C_{9}\times C_5)\rtimes(C_{19}\rtimes (C_9\rtimes C_2)).$$
 
Last edited:
  • #78
15,542
13,639
I'm pretty unsure about this solution. Linear algebraic groups over finite fields is new territory to me, but I think I managed to leverage some of my abstract algebra knowledge.

We start over the general finite field ##\mathbb{F}_q##:
$$|\mathrm{GL}(2,q)|=(q^2-q)(q^2-1)$$ a well known formula which can be deduced by fixing a nonzero vector for the first column (of which there are ##q^2-1##), and counting the number of linearly independent vectors as possible values for the second column (of which there are ##q^2-q## for each vector in the first column).

From here on out we assume that ##-1## is a nonresidue modulo ##q##, so that ##\mathbb{F}_q{[}i{]}## is a quadratic field extension with ##i^2=-1##. (##q=19## happens to satisfy this property.) We next make use of a representation of ##\mathrm{GL}(2,q)## over ##\mathbb{F}_{q^2}##. Choose the following basis for ##M(2,q)##: $$\mathbf{1} = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix},\quad \mathbf{i} = \begin{bmatrix} 0 & 1 \\ -1 & 0 \end{bmatrix},\quad \mathbf{j} = \begin{bmatrix} 0 & 1 \\ 1 & 0 \end{bmatrix},\quad \mathbf{k} = \begin{bmatrix} 1 & 0 \\ 0 & -1 \end{bmatrix}$$ Also known as the split-quaternions, we have a 2-dimensional representation over ##\mathbb{F}_{q^2}## via the following isomorphism:
$$w\mathbf{1}+x\mathbf{i}+y\mathbf{j}+z\mathbf{k}\Rightarrow\begin{bmatrix} w + xi & y + zi \\ y - zi & w - xi \end{bmatrix} = \begin{bmatrix} u & v \\ v^* & u^* \end{bmatrix}$$ The center of the split-quaternions consists of scalar matrices over ##\mathbb{F}_{q^2}##, of which there are ##q^2-1##. Hence, we have ##\mathrm{GL}(2,q)\triangleright\mathrm{PU}(Q,q^2)##. The latter group is the 2-dimensional projective unitary group with respect to the Hermitian form ##Q=\begin{bmatrix} 1 & 0 \\ 0 & -1\end{bmatrix}##, the form derived from the norm on the split quaternions ##|u|^2-|v|^2##. Its order is ##q(q-1)##.

We restate the following of the Sylow theorems for clarity: the number of conjugates of the Sylow ##p##-subgroup of a group ##G##, ##n_p##, satisfies ##n_p\equiv 1\, (\mathrm{modulo}\,p)## and ##n_p|[P : G]## where ##P## is any Sylow ##p##-subgroup.

The Sylow ##p##-subgroup of order ##q## can be generated by the element $$1+\frac{1}{2}(\mathbf{i}+\mathbf{j})$$which maps to the matrix ##\begin{bmatrix} 1 & 1 \\ 0 & 1 \end{bmatrix}## in the original representation over ##\mathbb{F}_q##. Observe that the Sylow ##q##-subgroup must be normal: ##n_q## divides ##q-1## and must have remainder 1 when divided by ##q##, implying the subgroup only has one conjugate. Since ##q## is prime, the Sylow ##q##-subgroup is isomorphic to ##C_q##.

Now we restrict our attention to the case ##q=19##. We have ##\mathrm{PU}(Q,q^2)\cong C_q\times G##, where ##|G|=19-1=2\cdot 3^2##. By inspection, we see that the Sylow ##3##-subgroup must be normal, since ##n_3## must divide ##2## and have remainder 1 when divided by ##3##. Note that the equivalence class of the element ##5+10\mathbf{j}## in ##\mathrm{PU}(Q,19^2)## has order ##9## (since the smallest ##n## such that ##(5+10\mathbf{j})^n## is scalar is ##9##), generating a cyclic subgroup of order 9, thus the Sylow ##3##-subgroup in ##G## is isomorphic to ##C_9##.

In total, we have ##\mathrm{GL}(2,19)\cong\mathbb{F}_{19^2}^\times\rtimes\mathrm{PU}(Q,19^2)##, and ##\mathrm{PU}(Q,19^2)\cong C_{19}\rtimes (C_9\rtimes C_2).## The composition factors are thus: $$\mathrm{GL}(2,19)\cong (C_{8}\times C_{9}\times C_5)\rtimes(C_{19}\rtimes (C_9\rtimes C_2)).$$
This is wrong. A short way to the answer is to factor out obvious normal subgroups, and deal with the rest.
 
  • #79
144
62
This is wrong. A short way to the answer is to factor out obvious normal subgroups, and deal with the rest.
I think I've now figured out how I'm supposed to do it, but I seem to have "proven" in my original proof that ##\mathrm{PSL}(2,q)## is not simple, which contradicts what I'm reading. I will take a closer look.
 
  • #80
mathwonk
Science Advisor
Homework Helper
2020 Award
11,242
1,447
A relevant result for prob. #7 seems to be Thm 8.3, chapter 8, page 296, of Mike Artin's Algebra. that PSL2(Z/19Z) is simple.
 
  • #81
15,542
13,639
A relevant result for prob. #7 seems to be Thm 8.3, chapter 8, page 296, of Mike Artin's Algebra. that PSL2(Z/19Z) is simple.
... in which case I want to know the name of the criterion for this result.
 
  • #82
mathwonk
Science Advisor
Homework Helper
2020 Award
11,242
1,447
not sure how to answer. mike just proves directly that any non trivial normal sub group is everything, by showing it must contain elements that generate the group. so,.."bare hands" criterion? there are 6 lemmas in the proof. He proves it for any field of characteristic not equal to 2, and containing at least 7 elements.
 
  • #83
84
29
Hello, I am Shreya Anish, Class X, India
This is my solution for question 15 for high schoolers

Please correct me if I am wrong
IMG_20210718_160313.jpg
 
  • #84
15,542
13,639
Hello, I am Shreya Anish, Class X, India
This is my solution for question 15 for high schoolers

Please correct me if I am wrong
View attachment 286166
Here is the reason why the formula is correct:

The evacuated Magdeburg hemispheres are affected by the difference of external and internal air pressure ##\Delta p## which presses them together. To calculate the total force on one of the two hemispheres, we consider a surface element ##dA##. The ambient air exerts a force ##d\vec{F}## on this area that is perpendicular to the surface element and of an amount ##dF=\Delta p\,dA\,.## However, we are only interested in the horizontal part of this force ##\vec{F}_{\|}## which is parallel to the direction to which the horses pull, i.e. parallel to the horizontal symmetry axis of the hemisphere. The perpendicular components ##\vec{F}_{\perp}## cancel themselves out. If we denote the angle ##\varphi## between the normal to the surface and the direction of pull, then the parallel component has an amount of
$$
dF_{\|} = dF\cdot \cos \varphi = \Delta p \;dA\cdot \cos \varphi =:\Delta p\; dA'=:dF'_{\|}
$$
The quantity ##dA'=dA\cdot\cos \varphi## can be viewed as parallel projection ot the surface area ##dA## onto a cylinder (see the figure).

MD_2.png


The parallel component ##dF'_{\|}## of the force which the air pressure exerts onto the projected surface area element ##dA'## is thus of the same amount as the parallel component ##dF_{\|}## of the original force exerts on the original surface element ##dA\,.##

The total amount of force exerted by the air pressure onto the hemisphere is the sum of all forces over the surface elements which compose the hemisphere. Since ##dF_{\|}=dF'_{\|}## we have for the total amount ##F_{air}=F'_{air}##, the force onto the projection. So the two hemispheres are pressed together as two cylinders were, whose diameters correspond to the section of the hemispheres: ##R##. The force of air pressure on a cylinder is easy to calculate. It's simply the product of pressure and circle area: $$F_{air}=F'_{air}=\Delta p \;A_{\circ}=\pi R^2 \Delta p$$
The example then calculates to a force of
$$
F_{air}=\pi \cdot (0.3)^2 (1.013-0.1)\;10^{5}\;N\approx 26\;kN
$$
which each group of horses has to come up with in order to separate the hemispheres. For comparison: One horsepower is approximately ##735.5## Watt, so ##30## horses would produce ##22\;kW##. A horse pulls with approximately ##10-12\,\%## of its weight, i.e. with ca. ##700\;N## or ##21\;kN## for ##30## horses.
 
  • #85
84
29
Here is the reason why the formula is
Thanks a Lot, fresh_42 !!! That was a really beautiful problem. Where can I get more such physics questions with interesting math?
 
  • #86
15,542
13,639
Good question. We will have 5 of those next month, however, I don't even remember where I got the one above from. I would look for physics olympiad questions, or google for mechanics exams or similar.
 
  • #87
84
29
For question Number 13, I think x=y=z=c/3
 
  • #88
125
48
13. Maximize ##f(x, y, z) = 4x^2y^2 - (x^2 + y^2 - z^2)^2## under the conditions ##x + y + z = c## and ##x, y, z > 0##.

Since ##z= c - (x+y)##, ##f(x, y, z)## can be expressed as a function of just the 2 variables, ##x, y##, i.e. as ##g(x, y) = 4x^2y^2 - (x^2 + y^2 - (c-x-y)^2)^2 = 4x^2y^2 - (c^2 + 2xy - 2cx - 2cy)^2##. To find the maximum or minimum value of ##g(x,y)## for a fixed value of ##y##, we equate the partial derivative of the function w.r.t. ##x## to 0 and solve for ##x##. $$
\frac {\partial g} {\partial x} = 8xy^2 -2(c^2+2xy-2cx-2cy)(2y-2c) = 16cxy - 8c^2x - 12c^2y + 8cy^2 + 4c^3
$$

Equating the partial derivative to zero yields $$
16cxy - 8c^2x - 12c^2y + 8cy^2 + 4c^3 = 0 \Rightarrow x = \dfrac {12c^2y - 8cy^2 - 4c^3} {16cy - 8c^2} =
\dfrac {3cy - 2y^2 - c^2} {4y - 2c}
$$

##\Rightarrow x_m = \dfrac {(2y - c)(y-c)} {-2(2y - c)} = \dfrac {c-y}{2}## where ##x_m## is the value of ##x## that yields minimum or maximum of ##g(x, y)## for a fixed value of ##y##. To find whether it is the minimum or maximum point, we need to consider the 2nd order partial derivative w.r.t. ##x##.

##\frac{\partial^2 g} {\partial x^2} = 16cy - 8c^2 = 8c(2y-c)##. Since ##c > 0##, this expression is positive if ##y > \frac{c}{2}## and negative if ##y < \frac{c}{2}##. Therefore, if ##x_m## would correspond to a maximum (for a fixed value of ##y##) if ##y < \frac{c}{2}##. (Observation 1)

Now ##g(x_m, y)## can be viewed as a function of just a single variable, ##y##.

$$
h(y) \equiv g(x_m, y) = f(\dfrac {c-y}{2}, y, c - y - \dfrac {c-y}{2}) = 4{\dfrac {c-y}{2}}^2 - y^4 = c^2y^2 - 2cy^3
$$

At the maxima and minima of ##h(y)##, the first order derivative would be zero, i.e. $$h'(y) = 0
\Rightarrow 2c^2y - 6cy^2 = 0 \Rightarrow 2cy(c - 3y) = 0
$$

Since ##c, y > 0##, the above equation implies that we must have ##c -3y = 0## as the only solution for ##h'(y)=0##, i.e. ##y = \dfrac{c}{3}##.

Now ##h''(y) = 2c^2 - 12cy = 2c(c - 6y)## and this expression takes a negative value when ##y = \dfrac{c}{3}##, hence ##y= \dfrac{c}{3}## must correspond to a maximal point, not a minimum. We also note that as per (Observation 1) too, ##x_m## will correspond to a maximum point of ##g(x, y)## (for a fixed ##y##) if ##y < \dfrac{c}{2}## and ##y = \dfrac{c}{3}## meets this condition too. Hence, ##f(x, y, z)## is maximized with ##y = y_m = \dfrac{c}{3}## and ##x = x_m = \dfrac{c-y_m}{2}## and ##z## derived using ##c - x - y##. In other words, the maximum is achieved with ##x = y = z = \dfrac{c}{3}## and this maximum value is ##f(\dfrac{c}{3}, \dfrac{c}{3}, \dfrac{c}{3}) = 3\left(\dfrac{c}{3}\right)^4 = \dfrac{c^4}{27}##
 
  • #89
15,542
13,639
Since ##z= c - (x+y)##, ##f(x, y, z)## can be expressed as a function of just the 2 variables, ##x, y##, i.e. as ##g(x, y) = 4x^2y^2 - (x^2 + y^2 - (c-x-y)^2)^2 = 4x^2y^2 - (c^2 + 2xy - 2cx - 2cy)^2##. To find the maximum or minimum value of ##g(x,y)## for a fixed value of ##y##, we equate the partial derivative of the function w.r.t. ##x## to 0 and solve for ##x##. $$
\frac {\partial g} {\partial x} = 8xy^2 -2(c^2+2xy-2cx-2cy)(2y-2c) = 16cxy - 8c^2x - 12c^2y + 8cy^2 + 4c^3
$$

Equating the partial derivative to zero yields $$
16cxy - 8c^2x - 12c^2y + 8cy^2 + 4c^3 = 0 \Rightarrow x = \dfrac {12c^2y - 8cy^2 - 4c^3} {16cy - 8c^2} =
\dfrac {3cy - 2y^2 - c^2} {4y - 2c}
$$

##\Rightarrow x_m = \dfrac {(2y - c)(y-c)} {-2(2y - c)} = \dfrac {c-y}{2}## where ##x_m## is the value of ##x## that yields minimum or maximum of ##g(x, y)## for a fixed value of ##y##. To find whether it is the minimum or maximum point, we need to consider the 2nd order partial derivative w.r.t. ##x##.

##\frac{\partial^2 g} {\partial x^2} = 16cy - 8c^2 = 8c(2y-c)##. Since ##c > 0##, this expression is positive if ##y > \frac{c}{2}## and negative if ##y < \frac{c}{2}##. Therefore, if ##x_m## would correspond to a maximum (for a fixed value of ##y##) if ##y < \frac{c}{2}##. (Observation 1)

Now ##g(x_m, y)## can be viewed as a function of just a single variable, ##y##.

$$
h(y) \equiv g(x_m, y) = f(\dfrac {c-y}{2}, y, c - y - \dfrac {c-y}{2}) = 4{\dfrac {c-y}{2}}^2 - y^4 = c^2y^2 - 2cy^3
$$

At the maxima and minima of ##h(y)##, the first order derivative would be zero, i.e. $$h'(y) = 0
\Rightarrow 2c^2y - 6cy^2 = 0 \Rightarrow 2cy(c - 3y) = 0
$$

Since ##c, y > 0##, the above equation implies that we must have ##c -3y = 0## as the only solution for ##h'(y)=0##, i.e. ##y = \dfrac{c}{3}##.

Now ##h''(y) = 2c^2 - 12cy = 2c(c - 6y)## and this expression takes a negative value when ##y = \dfrac{c}{3}##, hence ##y= \dfrac{c}{3}## must correspond to a maximal point, not a minimum. We also note that as per (Observation 1) too, ##x_m## will correspond to a maximum point of ##g(x, y)## (for a fixed ##y##) if ##y < \dfrac{c}{2}## and ##y = \dfrac{c}{3}## meets this condition too. Hence, ##f(x, y, z)## is maximized with ##y = y_m = \dfrac{c}{3}## and ##x = x_m = \dfrac{c-y_m}{2}## and ##z## derived using ##c - x - y##. In other words, the maximum is achieved with ##x = y = z = \dfrac{c}{3}## and this maximum value is ##f(\dfrac{c}{3}, \dfrac{c}{3}, \dfrac{c}{3}) = 3\left(\dfrac{c}{3}\right)^4 = \dfrac{c^4}{27}##
This is true in case ##x,y,z## are the side lengths of a triangle. The case ##c>z\geq x+y > y \geq x>0## is a bit more difficult (see discussion at the beginning of the thread).
 
  • #90
125
48
This is true in case ##x,y,z## are the side lengths of a triangle. The case ##c>z\geq x+y > y \geq x>0## is a bit more difficult (see discussion at the beginning of the thread).

In the proof I gave, I did not assume that ##x, y, z## must obey the triangle inequality. The only assumptions made are what are given in the question. I do not understand why the derivative-based solution will not help find the maximum if ##c>z\geq x+y > y \geq x>0##, mentioned above as the more difficult case. Was there an add-on to the original question which is mentioned in some post? Or is a simpler, more intuitive solution expected?
 
  • #91
15,542
13,639
In the proof I gave, I did not assume that ##x, y, z## must obey the triangle inequality. The only assumptions made are what are given in the question. I do not understand why the derivative-based solution will not help find the maximum if ##c>z\geq x+y > y \geq x>0##, mentioned above as the more difficult case. Was there an add-on to the original question which is mentioned in some post? Or is a simpler, more intuitive solution expected?
There is no maximum if the boundary is excluded, under the assumption I didn't make a mistake.

##c>z\geq x+y > y \geq x>0## makes ##f(x,y)\leq 0## and ##x=y=z=c/3## isn't a solution anymore because ##z=c/3< 2c/3 =x+y.##
 
  • #92
Q14 can be solved by dropping perpendiculars from B to s (let it meet at point L) , A to s (meet at point M) and C to s (meet at point N) . One can then see 3 sets of similar triangles. One set will give you AZ/BZ = AM/BL. Applying this 2 more times to the 2 other sets of similar triangles will give you the intended result.
 
  • #93
125
48
There is no maximum if the boundary is excluded, under the assumption I didn't make a mistake.

##c>z\geq x+y > y \geq x>0## makes ##f(x,y)\leq 0## and ##x=y=z=c/3## isn't a solution anymore because ##z=c/3< 2c/3 =x+y.##

The original question did not mention ##c>z\geq x+y > y \geq x>0##, so the proof of my earlier attempted answer did not impose that constraint, though it did take into account ##x, y, z >0## and ##x + y+ z = c##. I assume that the updated question only adds the constraint ##c>z\geq x+y > y \geq x>0## to the other conditions mentioned in the original question, so the condition ##x + y+ z = c## still holds true. If that is correct, below is my updated attempted solution

$$
f(x,y,z) = 4x^2y^2 - (x^2+y^2-z^2)^2 = (2xy - (x^2+y^2-z^2))(2xy + (x^2+y^2-z^2))
$$
$$
= (z^2 - (x-y)^2)((x+y)^2-z^2) = (z^2-(x-y)^2)(x+y-z)(x+y+z)
$$
$$
= -c(z^2-(x-y)^2)(z-x-y)
$$ (Eq. 1)

Since ##z \geq x+y## and ##x+y+z = c## and ##x,y,z>0##, we must have ##0 < x,y \leq \dfrac{c}{2} \leq z < c##. Hence, in Eq. 1, ##(z - x - y) \geq 0## and ##(z^2-(x-y)^2) > 0##, the latter since ##-\dfrac{c}{2} < (x-y) < \dfrac{c}{2} \leq z##. The expression ##-c(z^2-(x-y)^2)(z-x-y)## can therefore never take a positive value under the given constraints.
∴ ##f(x,y,z) \leq 0## under the given conditions. The maximum achievable value is 0, and this is achieved when ##z = \dfrac{c}{2}##, since this makes ##x+y = c - z = \dfrac{c}{2}## and hence ##(z-x-y)## in the product expression of (Eq. 1) becomes zero.
 
  • #94
125
48
11. Assume we have put a Cartesian coordinate system on France and got the following positions:
Paris ##(0, 0)##, Lyon ##(3, -8)## and Marseille ##(4, -12)##. Look up the definitions and calculate the distance between Lyon and Marseille according to
  • the Euclidean metric.
  • the maximum metric.
  • the French railway metric.
  • the Manhattan metric.
  • the discrete metric.

Euclidean metric (a.k.a. Euclidean distance) = ##\sqrt{(4-3)^2 + (-12 - (-8))^2} = \sqrt{1+16} \approx 4.123##
Maximum metric (a.k.a. Chebyshev distance) = ##\max{|4-3|, |-12 - (-8)|} = 4##
French railway metric = ##\|(3, -8)\| + \|(4, -12)\|## (since these 2 points are not collinear with ##(0, 0)##) = ##\sqrt{3^2 + (-8)^2} + \sqrt{4^2 + (-12)^2} \approx 21.193##
Manhattan metric = ##|(4-3)| + |-12 - (-8)| = 1+4 = 5##
Discrete metric = ##1##, since ##(3, -8) \neq (4, -12)##
 

Related Threads on Math Challenge - July 2021

Replies
56
Views
3K
Replies
102
Views
3K
Replies
67
Views
4K
  • Last Post
5
Replies
114
Views
3K
Replies
86
Views
6K
Replies
100
Views
2K
  • Sticky
  • Last Post
2
Replies
35
Views
728
Replies
137
Views
11K
M
Replies
101
Views
11K
Replies
16
Views
4K
Top